2019
DOI: 10.1038/s41598-019-46407-1
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Engineered to Express a Cardiomyocyte Binding Peptide Demonstrate Improved Cardiac Retention in Vivo

Abstract: Injury to the heart results in cardiomyocyte cell death and can lead to pathological remodeling of remaining cells, contributing to heart failure. Despite the therapeutic potential of new drugs and small molecules, there remains a gap in the ability to efficiently deliver cardioprotective agents in a cell specific manner while minimizing nonspecific delivery to other organs. Exosomes derived from cardiosphere-derived cells (CDCs) have been shown to stimulate angiogenesis, induce endogenous cardiomyocyte prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 32 publications
2
131
0
1
Order By: Relevance
“…A step forward is the use of induced pluripotent stem cells (iPSCs) derived MSCs as a renewable source of exosomes [139]. Another important step forward would be to enhance exosomal tropism for the cardiomyocytes [140]. The expression of the cardiomyocyte-specific peptide on the exosomal surface may improve homing-in of the delivered exosomes and promote their fusion with the recipient cardiomyocyte membrane as a mechanism for the delivery of their miR payload via endocytosis.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…A step forward is the use of induced pluripotent stem cells (iPSCs) derived MSCs as a renewable source of exosomes [139]. Another important step forward would be to enhance exosomal tropism for the cardiomyocytes [140]. The expression of the cardiomyocyte-specific peptide on the exosomal surface may improve homing-in of the delivered exosomes and promote their fusion with the recipient cardiomyocyte membrane as a mechanism for the delivery of their miR payload via endocytosis.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Several studies have been lately reported suggesting alternative strategies to functionalise EVs for more accurate targeting of the damaged heart [220,221]. These include: lentiviral vector-based engineering of secreting cells to upregulate the expression of cardiomyocyte-specific binding peptides fused to the murine transmembrane protein Lamp2b, in order to enrich the targeting epitope on the exosomal surface [222]; overexpression of exosomal CXCR4 to push their bioavailability towards the ischaemic heart [156]; membrane anchoring systems to directly dock tissue-specific antibodies or homing antigens on the EV surface [223,224].…”
Section: Looking For the Right Address: Improving Ev Cardiac Tropismmentioning
confidence: 99%
“…To promote the cardiac tropism of CDC-derived exosomes, CDCs are engineered to connect a cardiomyocytespecific binding peptide to the N-terminus of Lamp2b, which is a transmembrane protein on the exosomes. This engineered exosomes show better cardiomyocyte-specific uptake and enhanced protective effect [56].…”
Section: 2mentioning
confidence: 98%